Rodent models of early adversity: Impacts on developing social behavior circuitry and clinical implications - Packard, Katherine; Opendak, Maya (Frontiers in Behavioral Neuroscience, 2022)
Flexible and context-appropriate social functioning is key for survival across species. This flexibility also renders social behavior highly plastic, particularly during early development when attachment to caregiver can provide a template for future social processing. As a result, early caregiving adversity can have unique and lasting impacts on social behavior and even confer vulnerability to psychiatric disorders. However, the neural circuit mechanisms translating experience to outcome remain poorly understood. Here, we consider social behavior scaffolding through the lens of reward and threat processing. We begin by surveying several complementary rodent models of early adversity, which together have highlighted impacts on neural circuits processing social cues. We next explore these circuits underlying perturbed social functioning with focus on dopamine (DA) and its role in regions implicated in social and threat processing such as the prefrontal cortex (PFC), basolateral amygdala (BLA) and the lateral habenula (LHb). Finally, we turn to human populations once more to examine how this altered circuitry may play a role in social anhedonia, a common feature in diagnoses such as schizophrenia and major depressive disorder (MDD). We argue that this translational focus is critical for identifying specific features of adversity that confer heightened vulnerability for clinical outcomes involving social cue processing.